Effects of cage size on the natural behavior, serum parameters, production performance and hypothalamic mRNA expression profiles of laying hens - Yi Wan; Ruiyu Ma; Renrong Qi; Dawei Jiang; Helong Guan; Wei Liu; Junying Li; Yan Li; Kai Zhan (Poultry Science)
The objective of this study was to evaluate the effects of cage size on the natural behavior, serum biochemistry, production performance and hypothalamic transcriptome profiles of laying hens. A total of 360 79-week-old hens were selected and randomly assigned to three groups (with five replicates each) with different cage sizes: large cages (LCs), medium cages (MCs), and small cages (SCs). The stocking density remained consistent across all groups throughout the experimental period. Behavioral expression was evaluated through observation of only six birds per group on a weekly basis. Compared to the SC group, the average frequencies of walking, wing-flapping, feather-pecking and drinking significantly increased in the LC and MC groups (P <0.05), whereas the average frequency of stereotypic behavior significantly decreased (P <0.05), indicating that cage size has positive effects on natural behavior. The average daily step count (DSC) was in the order LC > MC > SC (P <0.05), which suggested an improvement in exercise ability in larger cages. The serum levels of MDA, CORT, AST and T-CH were significantly lower in the LC and MC groups than in the SC group (P <0.05), whereas the serum activities of SOD and GSH-Px were significantly greater (P <0.05). Additionally, compared to the SC group, the laying rates were increased by 1.61% and 2.20% (P <0.05), and the feed conversion ratio (FCR) were improved by 1.35% and 2.25%, respectively (P <0.05) in the LC and MC groups, respectively. In total, 437 and 81 differentially expressed genes (DEGs) were identified in the hypothalamus of birds between the LC and SC groups and the MC and SC groups, respectively. A majority of these DEGs were involved primarily in neuroactive ligand‒receptor interactions, focal adhesion and calcium signaling pathways, which are associated with the regulation of behavioral patterns, the stress response and follicular development. Our results suggest that an appropriate increase in cage size is beneficial to the natural behavior expression, health status and production performance of laying hens.